Mechanical characteristics and deformation mechanism of functionally graded triply periodic minimal surface structures fabricated using stereolithography. (15th October 2021) - Zhang, Cheng; Jiang, Zhaoliang; Zhao, Li; Guo, Weiwei; Jiang, Zongxiang; Li, Xinde; Chen, Guopeng
Highlights: The anisotropy of the functionally graded TPMS structures is modelled by the log-sigmoid function. Three types of functionally graded TPMS structures are discussed to mimic the mechanical properties of natural tissue. Functionally graded TPMS structures with I-WP type and low porosity has superior mechanical properties, inhibits dislocation slips, and controls the propagation of shear bands. Abstract: Triply periodic minimal surface (TPMS) structures have gained widespread applications because they offer a smooth surface and pore interconnectivity that meet biological and mechanical requirements and mimic native tissues. A novel design approach for functionally graded TPMS structures was proposed based on the log-sigmoid function, and these structures were successfully fabricated using stereolithography. The mechanical properties and deformation mechanism of three kinds of functionally graded TPMS structures were discussed. I-Wrapped Package (I-WP) type with low porosity exhibited a superior elastic modulus and yield stress than other structures. Compared with the Schwarz-P (P) and Gyroid (G) types, the Diamond (D) and I-WP types influenced the behaviors indicated by the stress-strain curves. A combination of stretching- and bending-dominated failure deformations was observed in functionally graded TPMS structures. I-WP type hindered dislocation slips and controlled the propagation of shear bands, whereas G and D types occupied a dominated status where shear bands spread to the unit cells in functionally graded TPMS structures. The mechanical properties were modified to the appropriate range in a specific region based on the functionally graded design, and this study exhibited tremendous potential for dental and other orthopedic implants. Graphical abstract: Image, graphical abstract